EKOLOGI ISLAM DAN PERUBAHAN IKLIM: TINJAUAN KRITIS TERHADAP PRAKTIK PERKEBUNAN SAWIT DI RIAU - Adi Sunarya; M. Ridwan Hasbi; Afrizal Nur (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
The oil palm plantation has been a major concern in discussions on climate change in Riau. The rapid development of the palm oil industry has had serious impacts on the environment, including climate change. Therefore, this study aims to analyze the impact of oil palm plantations on climate change in Riau, as well as to examine the perspective of the Qur’an on climate change. The research aims to explore the environmental impacts of oil palm land expansion, analyze the contribution of oil palm plantations to climate change in Riau, and examine the relevant Qur’anic verses on climate change in this context. This study uses a secondary data analysis approach from scientific literature, field observation data, and a study of Qur’anic verses related to climate change. The results show that the expansion of oil palm plantations has significantly contributed to climate change in Riau. Its impacts include deforestation, increased greenhouse gas emissions, and overall environmental degradation. In addition, the analysis of Qur’anic verses also provides interesting insights into the relationship between humans and nature.